Organization of work with electronic resources in libraries. - Khalafova, S. A. (Hileya: Scientific Bulletin / Gileya, 2016)
This article describes the organization of work with electronic resources in libraries in modern age, acquisition of modern libraries with electronic information resources. The article provides information on electronic information resources as CD-ROMs, multimedia educating programs, text books, full-text data bases, e– journals, e–books etc.